2020
DOI: 10.1111/tri.13778
|View full text |Cite
|
Sign up to set email alerts
|

eHealth in transplantation

Abstract: Summary eHealth (“electronic” Health) is a new field in medicine that has the potential to change medical care, increase efficiency, and reduce costs. In this review, we analyzed the current status of eHealth in transplantation by performing a PubMed search over the last 5 years with a focus on clinical studies for post‐transplant care. We retrieved 463 manuscripts, of which 52 clinical reports and eight randomized controlled trials were identified. Most studies were on kidney (n = 19), followed by liver (n = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 77 publications
0
20
0
8
Order By: Relevance
“…However, recent results of small trials implementing m‐Health apps or more complex technologies have reported no direct improvement on medication adherence 30,32,33 . Nevertheless, all these studies suggest that the implementation of e‐Health in current medical practice may also boost the use of m‐Health technologies 34 …”
Section: Discussionmentioning
confidence: 99%
“…However, recent results of small trials implementing m‐Health apps or more complex technologies have reported no direct improvement on medication adherence 30,32,33 . Nevertheless, all these studies suggest that the implementation of e‐Health in current medical practice may also boost the use of m‐Health technologies 34 …”
Section: Discussionmentioning
confidence: 99%
“…The pandemic highlights the advantages of such telemedicine and eHealth tools and could facilitate their broader implementation. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Hanke et al, 23 who reported on a telemedicine‐based aftercare program for kidney transplant recipients, concluded that this program was effective in maintaining physical activity and quality of life during the first wave of the COVID‐19 pandemic. The pandemic highlights the advantages of such telemedicine and eHealth tools and could facilitate their broader implementation 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…However, the additional advantage of new telemedicine concepts over standard posttransplant care must be demonstrated to justify the use of additional costs. 49 The development and implementation of these systems entail several different costs such as the cost of equipment, personnel, and communications. 50 Two of the most common methods of economic evaluation are cost‐utility analysis (CUA) and cost‐effectiveness analysis (CEA).…”
Section: Discussionmentioning
confidence: 99%